Intercultural Decision-Making Spaces in Chile, 1990-2022 - Fuentes, Claudio; Carril, Francisca; Yon, Rocío (Revista del CLAD Reforma y Democracia, 2023)
Chile is one of the few countries in Latin America that has not recognized indigenous peoples as constitutional. Despite this limitation, there has been a progressive legal development that has formalized their rights and participation in society. Taking an institutionalist-historical perspective, this article examines this evolution based on the analysis of more than a thousand legal bodies, several dozen committees, councils and commissions created to represent indigenous interests. A gradual densification of the formal frameworks regulating the rights of indigenous communities is observed in what has been called a “juridization of indigenous issues”. Moreover, this article systematizes more than 20,000 positions of representation to observe to what extent this “juridization” has an impact on a greater presence of indigenous representatives in positions of power. It is concluded that, despite the legal-formal densification, intercultural institutional spaces tend to be predominantly consultative and that a greater presence of them is observed at the local, rather than national, level. The work constitutes a relevant empirical contribution by systematizing for the first time the intercultural institutional spaces in the country. From a theoretical point of view, it confirms that the formalization of intercultural relations opens options for the development of new institutional dynamics. However, it also shows the resistance that exists in the development of new institutional dynamics.